Influence of High Pressure Homogenization on Free Fatty Acid Formation in Nannochloropsis sp. Issue 4 (12th February 2018) - Balduyck, Lieselot; Bruneel, Charlotte; Goiris, Koen; Dejonghe, Céline; Foubert, Imogen
Abstract : Although Nannochloropsis lipids have many potential applications in biofuels and high value products, their extraction is limited by the tough cell wall of this species. High pressure homogenization (HPH) can be used to improve the extraction efficiency. However, this can possibly induce free fatty acid (FFA) formation, which has a negative impact on oil quality. In this study, the HPH pressure and number of passes are varied in a full factorial design to study the impact of these factors on FFA formation, lipid extraction efficiency, and fatty acid profile. It is found that substantial amounts of FFA are formed during HPH treatments when compared to the non‐disrupted biomass. The FFA formation is mostly influenced by the number of passes applied, which can explained by a combined effect of the longer time residing as a wet paste and the temperature increase during the treatment. The large amount of FFA formed during the least intensive HPH treatment is in contrast with only a slight increase of the lipid extraction efficiency, which indicates that minor damage to the cell is sufficient to induce lipolytic reactions. The relative fatty acid profile after HI extraction is not influenced by the HPH treatment. Practical Applications : These results have important implications for the application of HPH treatments on microalgae with the aim to improve the extraction efficiency. It is demonstrated that more intensive HPH treatments with several passes are necessary to improve the extraction efficiency of Nannochloropsis lipids. However, the least intensive HPH treatments (1 pass at 400 bar) already induced the formation of substantial amounts of FFA. Consequently, to produce a biomass with a low FFA content and a high lipid extraction efficiency, a compromise should thus be made. High pressure homogenization (HPH) can efficiently be used to improve the extraction effiency of interesting compounds from Nannochloropsis cells. However, this treatment also induces the formation of free fatty acids (FFA), which have a negative influence on oil quality. Abstract : High pressure homogenization (HPH) can efficiently be used to improve the extraction effiency of interesting compounds from Nannochloropsis cells. However, this treatment also induces the formation of free fatty acids (FFA), which have a negative influence on oil quality.